Information support for the management of investment and innovation risks of an enterprise - Mykytyuk, Yuliia; Andrushkiv, Vitalii; Shmihel, Olha (Herald of Economics, 2025)
Introduction. Information support for investment and innovation risk management allows you to identify potential threats, carry out their quantitative and qualitative assessment, choose optimal response strategies, and track the results of decisions made in real time. Modern digital technologies, analytical tools, automated data collection and processing systems play a key role in forming a flexible, adaptive risk management model that covers both investment and innovation aspects of the enterprise’s activities. The purpose of the study is to substantiate the theoretical and methodological foundations and develop practical recommendations for the formation of an effective system of information support for the management of investment and innovation risks of the enterprise.Research methods. In the process of research, a set of general scientific and special methods was used, in particular: analysis and synthesis – to study the essence of investment and innovation risks and approaches to their information support; induction and deduction – to form conclusions regarding the improvement of the management system; comparative analysis – to assess the effectiveness of existing information systems at enterprises; graphical method – to visualize results; systemic approach – for a comprehensive justification of the structure of information support.Results. In the process of research, the essence and features of investment and innovation risks that arise in the activities of the enterprise in a dynamic market environment were outlined. The role of information support as a key tool for timely identification, assessment and minimization of such risks was considered. Existing approaches to the formation of an information base for risk management were analyzed, taking into account the specifics of innovation processes and investment projects. The structure of an information system is proposed, which includes internal and external data sources, processing and analytics tools, as well as mechanisms for supporting management decisions. The functional elements of an effective information system are characterized, which contribute to reducing the level of uncertainty in the implementation of investment and innovation activities of the enterprise.Prospects. Further scientific research should be directed to the development of adaptive models of information support, which will take into account the specifics of the industry affiliation of enterprises, the level of their digital transformation and the intensity of innovative activity.